2016
DOI: 10.18632/oncotarget.11895
|View full text |Cite|
|
Sign up to set email alerts
|

Loss ofZNF32augments the regeneration of nervous lateral line system through negative regulation ofSOX2transcription

Abstract: Human zinc finger protein 32 (ZNF32) is a Cys2-His2 zinc-finger transcription factor that plays an important role in cell fate, yet much of its function remains unknown. Here, we reveal that the zebrafish ZNF32 homologue zfZNF32 is expressed in the nervous system, particularly in the lateral line system. ZfZNF32 knock-out zebrafish (zfZNF−/−) were generated using the CRISPR-associated protein 9 system. We found that the regenerative capacity of the lateral line system was increased in zfZNF−/− upon hair cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…ZNF32 has been demonstrated to bind a conserved motif 5′-G(A/C/T)ATTT-3′ and diminish the regenerative capacity of the lateral line system in zebrafish through inhibition of SOX2 transcription. 45 There are two potential ZNF32 binding sequences in the TGFB1 gene promoter, and our results revealed that the mutation of ZNF32 binding site 1 (−1968 ~ −1962 bp) remarkably interrupted the decreased luciferase activity triggered by ZNF32, implying that ZNF32 negatively modulated TGFB1 transcription by directly binding to the −1968/−1962 region of the TGFB1 gene promoter. We also found that ZNF32 expression was inversely correlated with TGFB1 levels in patients with breast cancer and that silencing TGFB1 or treatment with an anti-TGF-βneutralizing antibody effectively reversed ZNF32 deficiency-mediated fibroblast activation and increased the growth of breast cancer cells triggered by CAFs.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…ZNF32 has been demonstrated to bind a conserved motif 5′-G(A/C/T)ATTT-3′ and diminish the regenerative capacity of the lateral line system in zebrafish through inhibition of SOX2 transcription. 45 There are two potential ZNF32 binding sequences in the TGFB1 gene promoter, and our results revealed that the mutation of ZNF32 binding site 1 (−1968 ~ −1962 bp) remarkably interrupted the decreased luciferase activity triggered by ZNF32, implying that ZNF32 negatively modulated TGFB1 transcription by directly binding to the −1968/−1962 region of the TGFB1 gene promoter. We also found that ZNF32 expression was inversely correlated with TGFB1 levels in patients with breast cancer and that silencing TGFB1 or treatment with an anti-TGF-βneutralizing antibody effectively reversed ZNF32 deficiency-mediated fibroblast activation and increased the growth of breast cancer cells triggered by CAFs.…”
Section: Discussionmentioning
confidence: 57%
“…55 Moreover, site-specific DNA methylation impeded the transcriptional activity of PDGF-A gene. 56 Our previous study demonstrated that ZNF32 negatively modulated the transcription of SOX2, 45 and SOX2 activation augmented PDGF-A level and tumorigenicity in GBM cells. 57 Therefore, we infer that ZNF32 may manipulate PDGF-A expression through SOX2.…”
Section: Discussionmentioning
confidence: 96%
“…As ZNF32 is a transcription factor in the zinc finger superfamily, we wondered whether ZNF32 can directly interact with the GPER promoter and regulate GPER expression at the transcriptional level. ZNF32 specific DNA binding sequence had been revealed as we previously described 42 . First, the GPER promoter (-5000 bp to + 100 bp) was analysed, and six potential ZNF32-binding sequences, G(A/T/C)ATTT, were found (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This class of nucleic acid binding proteins has a zinc finger domain interacting with DNA and thus, acts as transcription factor. While the target genes of two of the zinc finger proteins ( znfx1 and znf678 ) are unknown in zebrafish, a knock-down of znf32 suppresses the SOX2 transcription which in turn enhances the regeneration of the nervous lateral line system [ 57 ]. In other model organisms, these three zinc finger proteins are associated with cancer pathways and epigenetic methylation [ 58 61 ].…”
Section: Discussionmentioning
confidence: 99%